2011
DOI: 10.1002/fam.1088
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of the fire retardant mixture containing potassium carbonate using a cone calorimeter

Abstract: SUMMARYThis article presents the results of investigations obtained for a wood fire retardant agent which is currently under production. Experiments were conducted using a mixture of potassium carbonate and urea in accordance with the PN-C-04914 standard (the Polish equivalent of ISO 5660-1). Wood samples of Scots pine (Pinus sylvestris L.) were treated with the above mixture as well as with its individual components. It was observed that impregnation of samples with potassium carbonate and a mixture of potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…In mineralized wood, both peak HRR are substantially decreased and shifted to longer exposure times (Table 1), which indicates a lower fire growth rate and enhanced char stabilization. In essence, the PHRR values are reduced to a similar extent as in other fire-retardant systems reported in the literature (Simkovic et al 2005;Simkovic et al 2007;Hagen et al 2009;Grześkowiak 2012;Mahr et al 2012). As the mass loss values of unmodified and mineralized woods are comparable (Table 1), it can be assumed that the improved fire retardance of mineralized wood results from a combination of both physical and chemical effects.…”
Section: Resultssupporting
confidence: 71%
“…In mineralized wood, both peak HRR are substantially decreased and shifted to longer exposure times (Table 1), which indicates a lower fire growth rate and enhanced char stabilization. In essence, the PHRR values are reduced to a similar extent as in other fire-retardant systems reported in the literature (Simkovic et al 2005;Simkovic et al 2007;Hagen et al 2009;Grześkowiak 2012;Mahr et al 2012). As the mass loss values of unmodified and mineralized woods are comparable (Table 1), it can be assumed that the improved fire retardance of mineralized wood results from a combination of both physical and chemical effects.…”
Section: Resultssupporting
confidence: 71%
“…This trend was also confirmed by the bomb calorimetry measurements: the average values of the heat of combustion (HC) were lower for the protected wood than for the untreated material (Figure 7). Similar trends were reported elsewhere for the impregnation of wood samples with formulations containing potassium carbonate that resulted in longer times to ignition, reduced heat release rates, and lower values of heat of combustion [7,9]. Moreover, the snapshots taken from the video recordings of the cone calorimetry tests demonstrated that the protective coating containing K2CO3 made the flaming combustion of wood difficult to achieve (Figure S3), as opposed to the untreated surface.…”
Section: Resultssupporting
confidence: 85%
“…This effect is clearly visible in Figure 6, showing a blowing action of starch coating 20 s prior to ignition. The release of carbon dioxide not only diluted the mixture of flammable volatiles formed above the heated wood Polymers 2021, 13, 3841 9 of 12 surface but also provided a cooling effect [7]. This trend was also confirmed by the bomb calorimetry measurements: the average values of the heat of combustion (HC) were lower for the protected wood than for the untreated material (Figure 7).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Analysis of properties of fire retardants using a cone calorimeter was conducted by Kozłowski et al 26 and Grześkowiak. 27 Among the coating agents tested by Kozłowski et al, one was based on polyborate and polyphosphate salts with urea, another coating agent was based on polycondensation of the salt agent with silicates, while the third, a swelling agent, was based on ammonium resins with phosphates. In turn, Grześkowiak 22 tested a salt preparation based on potassium carbonate.…”
Section: Resultsmentioning
confidence: 99%